Study and Experimentation on Recycling of Dismantled Concrete (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Concrete is a combination of Cement, Natural sand, and Aggregates. Cement is a bindingproperty and a mixture of several chemical compounds. Aggregates are granites which areindigenous rocks which are excessively available. Natural sand is river sand which isdeclining day by day and its utilization is increasing day by day. Because of this reason it isespecially important to find an alternative for this problem. Dismantled RCC structureproduce heavy concrete waste is a waste. This is abundantly available and usually dumped inthe earth’s crust, due to which fertility of the soil decrease and land becomes useless, to avoidthis kind of problems concrete waste can be reused in the concrete and can be used inconstruction. Concrete waste can be partially replaced as coarse aggregate in construction.Based upon the requirement we can change the % of CA replaced by RCA so that theconstruction becomes economical, we can also use 100% RCA as CA for concrete walls usedas partisan walls as there will be no loads on the structure